Development of NMR Methodologies to Study Site Specific Zinc-Protein Interactions - Benton, Amy Musgrave (East Carolina University, 2021)
Found in all three biological domains of life and the second most abundant metal in the human body, zinc (Zn2+) is essential to various cellular processes like the metabolism of DNA and RNA, gene expression, and the regulation of apoptosis. However, as a d10 metal, Zn2+ is spectroscopically silent; electromagnetic radiation cannot induce d-to-d transitions. Current methodologies used to study zinc-binding proteins (ZBPs) include x-ray crystallography, NMR chemical shift monitoring, and amino acid substitutions studies. However, these all have limitations, like the inability to crystallize irregular and unstructured proteins, spectral overlap in NMR prohibiting assignment of residues, and the need to express of chemically synthesize several mutants. With the exception of x-ray crystallography, NMR and the study of mutants provide indirect information about the Zn2+ coordination sphere. The purpose of this research was to determine if the quadrupolar nucleus zinc-67 (67Zn2+) could be used in NMR experiments to more directly identify Zn2+-binding ligands. Two approaches were explored here, one based on 13C spin-lattice relaxation measurements (T1) and the other on the observation of spin-spin splitting in 1D 1H and 13C spectra. The model systems used for these experiments were ethylenediaminetetraacetic acid (EDTA), a carboxyl containing Zn2+ chelator; glycine (Gly), a simple amino acid; and PK9-H, a portion of the vacuolar cation-transporting ATPase (YPK9) protein shown to bind zinc. NMR studies of Zn-EDTA yielded 13C T1 values of 7.653 s (± 0.415), 409.650 ms (± 26.063), and 343.033 ms (± 38.171) for the carbonyl, lateral, and central carbons, respectively. 67Zn-EDTA had T1 values of 8.480 s (± 0.579), 454.167 ms (± 56.329), and 395.266 ms (± 66.944). The differences between Zn-EDTA and 67Zn-EDTA T1 values were statistically insignificant, indicating that 67Zn2+ did not significantly alter the spin-lattice relaxation of the nearby carbon atoms. No J-couplings between 67Zn and nearby atoms were readily observable in the 1D 1H and 13C spectra. If there is J-coupling, then it is likely very small ([mush less than] 1 Hz). The NMR studies of Gly showed that the addition of Zn2+ resulted in various Zn2+-bound species in solution and a loss in the carbonyl carbon signal. Therefore, it was deemed to be a poor system to use for these studies. Despite previous NMR research suggesting that the PK9-H peptide of YPK9 bound Zn2+, our CD and fluorescence studies showed no evidence of a binding interaction. However, a 13C NMR spectrum was recorded and the conditions for running solvent-suppressed 1H NMR and 2D 1H-1H TOCSY were optimized so that these experiments could be more easily completed in the future. In conclusion, there is no evidence that the utilization of 67Zn provides binding information about ligating atoms as it does not induce new splitting in NMR spectra and does not impact T1 values of atoms two or three bonds away from 67Zn. It is not recommended to pursue a heteronuclear TOCSY methodology using quadrupolar 67Zn. Further, Gly and YPK9 do not appear to be suitable model systems for these studies, as the former forms multiple Zn-bound species in solution and the latter shows little evidence of Zn-binding.
Keywords: spin-lattice relaxation; longitudinal relaxation; NMR; EDTA; ethylenediaminetetraacetic acid; zinc-67; zinc binding proteins; ZBPs; carbon-13; Yeast Vacuolar Cation-transporting ATPase; YPK9; glycine; Zinc; Proteins; Protein binding